Nutritional enhancement of cassava through processing: implications for sustainable food systems - Lambebo, Tagesse; Deme, Tesfaye; Geleta, Mulatu (Frontiers in Sustainable Food Systems, 2025)
Cassava (Manihot esculenta Crantz) is a vital food crop in Sub-Saharan Africa, Asia, the Pacific, and South America, serving as a staple for approximately 800 million people. While its roots are a rich energy source, its leaves contain valuable minerals, vitamins, and protein, offering potential to enhance starchy diets if properly processed to reduce toxic anti-nutritional factors. This study evaluated the nutritional profiles of cassava roots and leaves and assessed the role of processing in improving nutrient retention and safety. Two varieties, kello and qulle, obtained from the Areka Agricultural Research Center, were analyzed. Roots and leaves were subjected to fermentation, boiling, and fluidized bed drying, followed by nutritional, anti-nutritional, and functional characterization using AOAC standard methods. Results showed that roots had higher carbohydrate content (81.0–87.1 g/100 g), while leaves exhibited superior protein (21.2–28.4 g/100 g), fiber (16.1–22.9 g/100 g), carotenoids (234.1–987.9 μg/g), and essential minerals, including calcium (499.8–545.4 mg/100 g), potassium (1193.4–1211.0 mg/100 g), magnesium (274.5–340.5 mg/100 g), and iron (129.1–146.1 mg/kg). Anti-nutritional factors, including cyanide (10.1–61.0 mg/kg in leaves vs. 1.8–47.5 mg/kg in roots), condensed tannins, oxalates, and phytate, were higher in leaves but significantly reduced through processing. Fermentation followed by boiling and drying decreased cyanide levels by up to 83.4%, while tannins, oxalates, and phytate were reduced by 59.6, 83.4, and 88.9%, respectively. Variety kello demonstrated a better overall nutritional profile than qulle, except for carotenoids, which were higher in qulle. These findings highlight the influence of genetic background and processing techniques on cassava’s nutritional quality. To optimize cassava’s dietary benefits, further research should explore diverse germplasm and refine processing methods to maximize nutrient retention while minimizing anti-Xnutritional factors.